2022
DOI: 10.56303/jhnresearch.v1i1.20
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Socio-Demographic Factors with the Incidence of Stunting in Elementary School Children in Rural Enrekang

Abstract: Objective: Stunting is a major health emergency in most developing countries, including Indonesia. The total number of stunting children in 2019 in Enrekang Regency is quite high at 44.8%. Therefore, this study aims to determine the relationship between maternal knowledge, maternal education level, and the number of family members with the incidence of stunting in elementary school children in rural Enrekang, South Sulawesi. Method: An analytical observational study with a cross sectional approach. The subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…Family residence was a factor related to stunting events. In this study families who have toddlers and stay away from health, facilities are more at risk of stunting (Abri, 2022). This was because the geographical condition of the family residence is very influential in the family's ease to reach health facilities, Posyandu, children's family development and also influence the cadres to visit the toddler.…”
Section: Discussionmentioning
confidence: 88%
“…Family residence was a factor related to stunting events. In this study families who have toddlers and stay away from health, facilities are more at risk of stunting (Abri, 2022). This was because the geographical condition of the family residence is very influential in the family's ease to reach health facilities, Posyandu, children's family development and also influence the cadres to visit the toddler.…”
Section: Discussionmentioning
confidence: 88%
“…This nutritional education media can help stimulate the sense of the eye (vision) during the education process. Knowledge is the initial capital of a mother who is used to provide adequate nurturing to her children (22).…”
Section: The Effect Of Exclusive Breastfeeding Education On Changes I...mentioning
confidence: 99%
“…Various studies in Indonesia have revealed that the incidence of nutritional problems is a multifactor problem. Non-exclusive breastfeeding in the first 6 months of life, low parental education, low economy, lack of parental knowledge and clean and healthy living behaviour(12)(13) (14).…”
Section: Introductionmentioning
confidence: 99%